Dynamics of Young Generation Preferences in Halal Tourism: Synthesis of the Book Youth and Halal Tourism Research - Prihatmadji, Wiwiet; Syamsurizal; Caniago, Aspizain; Maulamin, Taufan; Chaerunisyah, Ana (Lead Journal of Economy and Administration, 2025)
Young generations, particularly Generation Z and Millennials, are the primary drivers of the rapid expansion of global halal tourism. As the halal industry continues to grow, understanding the preferences and behaviors of young Muslim travelers has become crucial, especially as they represent the largest demographic segment in many Muslim-majority countries. This study synthesizes the key findings of the Youth and Halal Tourism Research book—an academic work involving multiple universities—while integrating additional insights from recent studies on halal consumption behavior among Indonesian youth. The results indicate that halal food and beverages are the most influential factors shaping youth preferences in halal tourism. Other significant factors include Sharia-compliant hotel facilities, religious-spiritual experiences, and interactions with digital technologies such as VR-based tourism. This study contributes a comprehensive overview of the dynamics of halal tourism preferences among young generations, providing valuable insights for policymakers and industry stakeholders who aim to design tourism services aligned with the values and expectations of today's digital-native youth.